ภาวะสุขภาพจิตของพนักงานเก็บขยะในกรุงเทพมหานคร - นรารัตน์ ธนกุลพรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
This study was a cross-sectional descriptive study. The objectives of this study were to study mental health and factors related to mental health of waste collectors in Bangkok Metropolis. The samples of the study were 439 collectors of the Public Cleansing Department of the B.M.A. The instrument was a set of questionnaires consisting of 2 pats: demographic questionnaire and GHQ-30 (General Health Questionnaire 30) Data was analyzed by SPSS for Windows. Statistics utilized were percentage, mean, standard deviation, maximum, minimum, Chi-square test and Multiple Logistic Regression Analysis. The Study revealed that 21.2 percent of waste collectors had mental health problem. Factors related to mental health were financial status, debt, physical health problem and hours of work per day were statistically significant related to mental health of waste collectors at p<0.01. The factors significantly predicted mental health after performing multiple logistic regression analysis were financial status, physical health problem and hours work per day at the 0.01 level and debt at the 0.05 level.